2008
DOI: 10.1364/oe.16.001777
|View full text |Cite
|
Sign up to set email alerts
|

A polarizer-free flexible and reflective electro-optical switch using dye-doped liquid crystal gels

Abstract: A polarizer-free flexible and reflective electro-optical switch using dye-doped liquid crystal (LC) gels is demonstrated. The electro-optical performances of both scattering and absorption based dye-doped LC gels depend on curing temperatures due to domain sizes of polymer networks. Such flexible electro-optical switch is bendable and trim-able because of the vertical polymer networks and gel-like materials. The dye-doped LC gel shows good reflectance ~55%, good contrast ratio~450:1 and fast response~6.4 ms at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(31 citation statements)
references
References 32 publications
1
30
0
Order By: Relevance
“…//I 1 1 / / / [5], this pretilt angle was provided by rubbing alone. We attempted to reproduce their experimental results using rubbing method.…”
Section: ) Operation Principle Of Va-pslcmentioning
confidence: 99%
See 1 more Smart Citation
“…//I 1 1 / / / [5], this pretilt angle was provided by rubbing alone. We attempted to reproduce their experimental results using rubbing method.…”
Section: ) Operation Principle Of Va-pslcmentioning
confidence: 99%
“…This strong scattering effect was proposed and developed for potential applications where high light efficiency was required since no polarizers were needed in these devices [4]. However, it has also recently been shown that [5], by adding a pretilt angle to this VA-PSLC mode, e.g. using rubbing method, it is possible to reduce the scattering significantly while fast response time and good contrast ratio can still be obtained.…”
Section: ) Introductionmentioning
confidence: 99%
“…The materials we employed are negative liquid crystal (ZLI-4788, Merck), a diacrylate monomer with a dichroic dye S428 (Mitsui, Japan) at 90:5:5 wt% ratios. The sample preparation process is similar to the previous one [22]. The cell gap was 5 mm.…”
Section: Mechanism and Optical Analysis Of Polarizer-free Dye-dopmentioning
confidence: 99%
“…Based on the combination of scattering and absorption we have recently developed polarizer-free LCDs using dye-doped dual frequency liquid crystal gels [19,20] and flexible dye-doped LC gels [21,22] with high contrast and fast response.…”
mentioning
confidence: 99%
“…However, the electro-optical performance of dye-doped PDLCs is limited due to the dye molecules entangled in the polymer matrix, the order parameter of the dichroic dye and the dichroic ratio (typically ~10:1) of the dye. To avoid the problem of solubility between dye and polymer matrix, we have developed a polarizer-free electro-optical switch using a dye-doped dual-frequency liquid crystal (DFLC) gel and dye-doped LC gels [6,7,8,9]. Without polarizers, the optical efficiency is high and the viewing angle is wide.…”
Section: Introductionmentioning
confidence: 99%